IMPLEMENTASI MEDIA CERITA BERGAMBAR INTERAKTIF DALAM MENINGKATKAN KECERDASAN EMOSIONAL BAGI ANAK USIA DINI USIA 5 - 6 TAHUN - Eka Wulandari; Mastikawati; Fitriah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has significantly influenced the social and emotional development of early childhood, particularly due to increased exposure to digital devices that reduces direct social interaction. This condition requires teachers to employ engaging learning media capable of stimulating children's emotional intelligence. This study aimed to describe the implementation of interactive illustrated story media in improving the emotional intelligence of children aged 5–6 years at TK Negeri Pembina Muaro Jambi. The study employed a descriptive qualitative approach involving 15 children in Group B and one classroom teacher as research participants. Data were collected through observation, interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that the implementation of interactive illustrated story media enhanced children's ability to recognize, understand, and regulate emotions, foster empathy, and improve social skills through storytelling activities involving active interaction between teachers and children. Observation results indicated that 9 children (80%) achieved the Developing as Expected category, 3 children (30%) reached the Very Well Developed category, 2 children (20%) were Beginning to Develop, and 1 child (10%) remained Not Yet Developed. Therefore, interactive illustrated story media can be considered an effective learning strategy for enhancing early childhood emotional intelligence through enjoyable, meaningful, and contextual learning experiences.